Cardiac reserve by 6-minute walk stress echocardiography in systemic sclerosis. Issue 1 (19th February 2021) - Arase, Miharu; Kusunose, Kenya; Morita, Sae; Yamaguchi, Natsumi; Hirata, Yukina; Nishio, Susumu; Okushi, Yuichiro; Ise, Takayuki; Tobiume, Takeshi; Yamaguchi, Koji; Fukuda, Daiju; Yagi, Shusuke; et al.
Abstract : Objectives: There is a high prevalence of left ventricular diastolic dysfunction (LVDD) in systemic sclerosis (SSc) which is associated with high mortality. Thus, early detection of LVDD could be important in management of SSc. We hypothesised that exercise echocardiography in SSc patients with normal resting haemodynamics may expose early phase LVDD, which could affect its prognosis, defined as cardiovascular death and unplanned hospitalisation for heart failure. Methods: Between January 2014 and December 2018, we prospectively enrolled 140 patients with SSc who underwent 6-minute walk (6MW) stress echocardiographic studies with normal range of estimated mean pulmonary arterial pressure (mPAP) (<25 mm Hg) and mean pulmonary artery wedge pressure (mPAWP) (<15 mm Hg) at rest. We used ΔmPAP/Δcardiac output (CO) to assess pulmonary vascular reserve and ΔmPAWP/ΔCO to assess LV cardiac reserve between resting and post-6MW. Results: During a median period of 3.6 years (IQR 2.0–5.1 years), 25 patients (18%) reached the composite outcome. Both ΔmPAP/ΔCO and ΔmPAWP/ΔCO in patients with events were significantly greater than in those without events (8.9±3.8 mm Hg/L/min vs 3.0±1.7 mm Hg/L/min; p=0.002, and 2.2±0.9 mm Hg/L/min vs 0.9±0.5 mm Hg/L/min; p<0.001, respectively). Patients with both impaired LV cardiac reserve (ΔmPAWP/ΔCO>1.4 mm Hg/L/min) and impaired pulmonary vascular reserve (ΔmPAP/ΔCO>3.0 mm Hg/L/min) had worse outcomes compared with those without these abnormalities (p<0.001). Conclusion: The 6MW stress echocardiography revealed impaired LV cardiac reserve in SSc patients with normal resting haemodynamics. Furthermore, LV cardiac reserve independently associates with clinical worsening in SSc, providing incremental prognostic utility, in addition to pulmonary vascular parameters.